One‐step fabrication of bulk nanocomposites reinforced by carbon nanotube array fragments. Issue 1 (21st October 2021) - Aly, Karim; Aboubakr, Sherif H.; Bradford, Philip D.
Abstract: Vertically aligned carbon nanotube (VACNT) array growth is an established process where high aspect ratio carbon nanotubes (CNTs) are produced. This work demonstrates one‐step approach to fabricate bulk polymer nanocomposites using CNT array fragments'. Here, 4.5 mm long CNTs were collected post VACNTs synthesis. Next, CNT array fragments were coated with pyrolytic carbon (PyC) and infused with polydimethylsiloxane (PDMS) matrix to create porous CNT/PDMS nanocomposite with a CNT weight fraction of 20%. Achieving similar weight fraction with super long bundled CNTs using dispersion techniques is extremely difficult. The compression and dynamic mechanical behaviors and piezoresistive response of the PDMS filled nanocomposite were assessed. The results revealed the potential of the synthesized structure to serve as fatigue‐resistant pressure sensors with high damping and self‐sensing capabilities. The proposed fabrication technique is versatile, as it can work with thermosetting and thermoplastic polymers in addition to allowing for mass production of PDMS filled nanocomposites. Abstract : This study presents an easy and versatile method to prepare 3D porous PDMS nanocomposites reinforced with carbon nanotube (CNT) array fragments waste produced during the synthesis of high aspect ratio CNTs. Notably, the proposed technique allows for reutilizing CNTs waste effectively as it produces bulk nanocomposites that exhibits high stiffness, improved compression strength, structural stability and recoverability. Moreover, the resulting PDMS nanocomposites also exhibit enhanced damping and self‐sensing capabilities which demonstrate the multifunctionality of the synthesized polymer nanocomposite.